Utilization of Conservation Forest Areas in Taman Wisata Alam Gunung Batur Bukit Payang in The Perspective of Natural Tourism Entrepreneurship Permits - I Gusti Bagus Sudiantara; I Wayan Wesna Astara; Ni Made Jaya Senastri (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
BKSDA Bali faces problems in the development of natural tourism in Taman Wisata Alam Gunung Batur Bukit Payang (TWA GBBP), namely the business of providing natural tourism facilities (hot springs) without permission by Batur Customary Village. The hot spring has been managed since 1986 and developed into Batur Natural Hot Spring in 2007. The issues discussed in this study are: (1) How is the licensing process for the use of conservation forest areas in the development of natural tourism in Taman Wisata Alam Gunung Batur Bukit Payang? (2) What is the model of community-based natural tourism development in Taman Wisata Alam Gunung Batur Bukit Payang? The methods used in this study are a type of empirical legal research, using the approach of legislation, the historical juridical approach and the legal sociology approach. Based on the results of the analysis, it can be concluded that the process of licensing the utilization of the area in TWA GBBP is based on: (1) Inventory of regional potential, (2) Arrangement of the area into the management block, set on February 11, 2016, (3) The design of natural tourism sites on the utilization block, set on June 4, 2018, (4) The preparation of the management plan (RPJP) of KPHK Kintamani was set for April 15, 2019. Taman Wisata Alam Gunung Batur Bukit Payang is eligible for natural tourism business licensing in the form of IUPJWA / PB-PJWA and IUPSWA / PB-PSWA. There are three models of community-based natural tourism development in Taman Wisata Alam Gunung Batur Bukit Payang, namely: (1) Hot Spring Tourism (Batur Natural Hot Spring) developed by Batur Customary Village and accommodated through cooperation with PT. Tanaya Pesona Batur through IUPSWA commitment, (2) Camping Tourism developed by Pokdarwis Ampupu Kembar, (3) Mount Batur Climbing Tour developed by FP3GB through the provision of IUPJWA.